Fryzjer czy fryzjerka? Rodzaj gramatyczny nazwy zawodu jako nośnik statusu społecznego - Kamasa, Victoria (Investigationes Linguisticae, 2007)
This article is a report of the results of qualitative research related to the influence of gender of a profession name on the social status of women who use this name. The subject is analyzed in two ways ? firstly quantitatively to show the connections between social status related to gender of professions names and different variables, and then qualitatively ? to show the character descriptions associated with women, who use profession names in different gender and types of attitudes observed between the respondents.